Robotically Assisted Gynecologic Surgery: 2-Year Experience in the French Foch Hospital - Goetgheluck, Julie; Carbonnel, Marie; Ayoubi, Jean Marc (Frontiers in Surgery, 2014)
Robotically-assisted laparoscopic surgery has seen rapid expansion over the past few years and it constantly evolves with a progressive enlargement of its range of indications. In the present paper we would like to share our 2-years experience regarding the use of robotic in various laparoscopic procedures, including hysterectomy, myomectomy, adnexal surgery, and sacrocolpopexy.